Acute necrosis after Gamma Knife surgery in vestibular schwannoma leading to multiple cranial nerve palsies. (August 2016) - Kapitza, Sandra; Pangalu, Athina; Horstmann, Gerhard A.; van Eck, Albert T.; Regli, Luca; Tarnutzer, Alexander A.
Highlights: Acute necrosis is a rare complication after Gamma knife radiosurgery of vestibular schwannoma. We present a single patient with acute vestibulocochlear and facial neuropathy 48 hours after treatment. MRI was suggestive for acute radiation necrosis with contrast sparing within the schwannoma. Steroids may be considered based on degree of accompanying edema. Abstract: We discuss a rare acute complication after Gamma Knife therapy (Elekta AB, Stockholm, Sweden) in a single patient. A 52-year-old woman presented with vertigo, facial weakness and hearing loss emerging 48 hours following Gamma Knife radiosurgery for a right-sided vestibular schwannoma. Neurological examination 6 days after symptom onset showed right-sided facial palsy, spontaneous left-beating nystagmus and pathologic head-impulse testing to the right. Pure-tone audiogram revealed right-sided sensorineural hearing loss. A diagnosis of acute vestibulocochlear and facial neuropathy was made. Brain MRI demonstrated focal contrast sparing within the schwannoma, likely related to acute radiation necrosis. Acute multiple cranial neuropathies of the cerebellopontine angle after Gamma Knife treatment should raise suspicion of acute tissue damage within the schwannoma and should result in urgent MRI. Treatment with steroids may be considered based on accompanying swelling and edema.